A terpyridine-based chemosensor for detection transition metal ions in aqueous solution: Synthesis and characterization. (5th October 2021) - Liu, Pan; Chi, Zheng; Shi, Ganhui; Dong, Hao; Ma, Chenchen; Chen, Xuegang
Graphical abstract: Highlights: Preparation of novel hydrophilic polymers incorporated with terpyridine and conjugated fluorescence segments. These polymers exhibit blue emission and the interaction between the polymers and Zn 2+ and Cd 2+ leads to emission reinforcement. The polymers show fluorescence quenching resulted from binding Fe(II) ions and new strong absorption peaks around 570 nm. Based on appearance and PL changes, these polymers can be ideal chemisensors to detect transition metal ions in aqueous environment. Abstract: A hydrophilic terpyridine-based copolymer chemosensor containing acrylic acid and fluorescence fragments to detect transition metal ions in aqueous solution were synthesized and well characterized. Characteristic color changes, which were resulted from chelating with specific metal ions and visible to the naked eye under natural and ultraviolet light provided possibility for real-time monitoring. Absorption and luminescence properties were adopted for further study, which exhibited unique response when treated with various metal ions. Intensity of absorption peak at 284 nm decreased with the increase of all kinds of metal ions while the secondary absorption peak at 335 nm increased with a certain concentration range. Different metal ions bring fluorescence enhancement or quenching response to the copolymer in aqueous solution. The unique fluorescence enhancing resulting from coordination of terpyridine and Zn 2+ endows the polymer excellent detection ability. In particular, owing to metal-ligand charge transfer (MLCT) process, a new absorption peak appeared at 570 nm with the addition of Fe 2+, and the polymer showed obvious color change.